A convenient synthesis, biological activity and X-ray crystallography of novel α-aminophosphonate derivatives. (11th November 2022) - Bahadi, Rania; Boughoula, Rahma; Berredjem, Malika; Bachari, Khaldoun; Bouzina, Abdeslem; Bouacida, Sofiane; Sbartai, Hana; Benalliouche, Fouzia; Redjemia, Rayenne
Abstract: A new series of novel α-aminophosphonate derivatives have been synthesized by new rapid and convenient approach, based on the stepwise one pot reaction of 2-hydroxyaniline, aromatic aldehydes and triethyl phosphite. The structures of all compounds have been identified by appropriate spectroscopic methods such as FTIR, 1 H, 13 C, 31 P NMR and ESI-MS. The crystal structure of diethyl-(2-fluorophenyl)-(2-hydroxy-4-methylphenyl)amino phosphonate has been determined, it crystallizes in the P -1 space group. In vitro antifungal activity of the synthesized compounds were tested against wheat fusarium ( Fusarium oxysporum ) and compared with standard antifungal drug Chlorpyriphos EC to explore their potential antifungal activity. We also measured the antioxidant activity of these molecules, compared with vitamin C as standard antioxidant. Graphical Abstract: UF0001